Tectonics of the Solomon Sea Basin from Vertical Gravity Gradient and Seismic Data. (28th April 2023) - GONG, Wei; XING, Junhui; MENG, Qingwei; XING, Lei; XU, Chong; ZHANG, Hao
Abstract : Abstract: The Solomon Sea Basin is a Cenozoic back‐arc spreading basin within the convergence system of the Pacific and Indo‐Australian plates. Against the background of subduction polarity reversal, the current Solomon Sea Basin gradually formed a rhombic morphology with the subduction of the basin along the New Britain Trench and the Trobriand Trough. By analyzing the vertical gravity gradient, natural earthquake and seismic reflection data, this study determines the structural characteristics of the Solomon Sea Basin. It was found that the tectonics of the basin are characterized by the original expansion structure within the central part in addition to the structure induced by the latest subduction along the basin margin. The original spreading structure of the basin presented an east–west linear graben and horst controlled by normal faults during the basin expansion period. As a result of the subduction and slab‐pull of the Solomon Sea Basin, extensional structure belts parallel to the New Britain Trench formed along the basin margin.